2016
DOI: 10.24846/v25i2y201606
|View full text |Cite
|
Sign up to set email alerts
|

Solving a Novel Multi-Objective Inventory Location Problem by means of a Local Search Algorithm

Abstract: Problems in operations research are usually modelled as single objective ones even though there exist several goals that should be attained. Multiple reasons of why inherently multi-objective problems are modelled as single objective can be identified: better understanding of the problem features, simplification of the mathematical formulation of the problem, among others. However, summarising (usually conflicting) objectives into one objective function can be a sign of over-simplification in the problem model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the study of Huang & Lin (2010) In the study (Hnaien et al, 2016), a branch-andbound algorithm performed better than a heuristic algorithm. In the study (Lagos et al, 2016), an inventory model with objectives of minimizing warehouse location and general inventory management costs was solved by Pareto local search. It was concluded that Pareto local search is effective for such a problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study of Huang & Lin (2010) In the study (Hnaien et al, 2016), a branch-andbound algorithm performed better than a heuristic algorithm. In the study (Lagos et al, 2016), an inventory model with objectives of minimizing warehouse location and general inventory management costs was solved by Pareto local search. It was concluded that Pareto local search is effective for such a problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comparison of the proposed algorithm with other well-known heuristic algorithms, including nondominated sorting genetic algorithm-II (NSGA-II) [31] and multiobjective evolutionary algorithm (MOEA) [67], is performed in this section to test the proposed IMOPSO. Benchmark instances are utilized to solve and analyze with three objectives; in this case, the total waiting time and number of vehicles can be exchanged and represented by the penalty and vehicle maintenance costs on the basis of relative research that imbalances the multiobjective and single-objective problems [68,69]. The proposed algorithms along with two other algorithms are performed on a laptop with an Inter (R) Core (TM) i7-8565 1.8 GHz CPU and 8GB RAM using MATLAB programming language.…”
Section: Algorithm Comparisonmentioning
confidence: 99%
“…Therefore, papers are also continuously dealing with uncertainty in inventory control [8], [24]. As a result of the emergence of complex inventory control systems, scientist began to use the methods of multi-criteria optimization: [25], [14], [16], [19].…”
Section: Introductionmentioning
confidence: 99%